Pendugaan Cadangan Karbon (C) Tersimpan Di Atas Permukaan Tanah Pada Vegetasi Hutan Tanaman Jati (Tectona grandis Linn. f )(Di RPH Sengguruh BKPH Sengguruh KPH Malang Perum Perhutani II Jawa Timur) - Mochammad Chanan (Jurnal Gamma, 2012)
Pendugaan Cadangan Karbon (C) Tersimpan Di Atas Permukaan Tanah Pada Vegetasi Hutan Tanaman Jati (Tectona grandis Linn. f )(Di RPH Sengguruh BKPH Sengguruh KPH Malang Perum Perhutani II Jawa Timur)Mochammad ChananStaf Pengajar Jurusan Kehutanan, Fakultas Pertanian PeternakanUniversitas Muhammadiyah Malang email : chanan@umm.ac.idABSTRACTThe purpose of this study to determine the potential of carbon stored in plants teak (T. grandis Linn.f). and to determine the age class (KU) how many of the greatest stores of carbon in the northern part RPH Sengguruh BPKH Sengguruh KPH Malang.This study was conducted in July 2011 to June 2012 took place dilahan Perhutani Northern RPH Sengguruh BPKH Sengguruh KPH Malang, laboratory analysis performed Forestry Biomass Muhammadiyah University of Malang (UMM). The tools used in this study were the scales, oven, pole vault, plastic bags, cameras, phi band, meter, machetes / knives, scissors, kristin meter, plastic rope, tally sheets and stationery. The materials used are the branches of trees and plants to be analyzed in the laboratory.Calculation results of estimation of carbon stored in vegetation Plantation Teak (T. grandis Linn.F) this is expected to serve as the basis for calculating estimates of the carbon in the Teak Forest Vegetation in the National Scale.Key word : carbon, Forest Vegetation